Daylight Guidance Systems - Muhammed Engin Çiftçi; Ümit Arpacıoğlu (Journal of Architectural Sciences and Applications, 2021)
Sustainable architecture concept and renewable energy sources begin to take places in to the building life cycle. Renewable energy sources are critical in terms of energy saving and using efficient of useable natural energy sources. With the idea of using the light in spaces actively, it is intended to save energy and create a comfortable space. During the ongoing process with the advancement of technology, people’s demand for comfort has increased. Daylight guidance systems developed to provide the climatic and visual comfort conditions, reduce the energy consumption and minimizing the damage dealt to the environment. This study aims to show the contribution of the daylight guidance systems that are being started to develop in the 19th century, to meet the need for interior lighting and comfort. It also shows the possible benefits of these systems in the case of usage in today’s architecture.